Desa Electric Enterprise (electrical and wiring services) / Susheela Saila Sunid ... [et al.] - Sunid, Susheela Saila; Muhamad Azlan, Hafizah; Mohd Darwis, Nur Zaidani Wati; Ariffin, Ariza Farhana (2007)
DESA Electric Enterprise is partnership companies where the main businesses are providing services for residential area, private developers, and government contractors. This company name is based on shareholder name. We are the only and the first lady owners of Bumiputra company which taken the opportunity to provide the electrical and wiring services. So, we take this initiative to involve in these industries and to compete with other competitors. With these services, the need of electricity of Kedah and Perlis will no longer have to face the disturbance of the electricity breakdown.